Structure of technology evolution: The way on which ICT industry emerged in Korea - Kibae Kim; Sungdo Jung; Changjun Lee; Junseok Hwang (International Telecommunications Society (ITS), 2013)
The role of ICT in the economic growth in Korea is a great attraction to the telecommunication society interested in the relationship among ICT, innovation policy and economic growth. However, prior research concentrates on investigating the effect of policy on innovation and economic growth, but misses the mechanism how a policy affects the technological system which interacts with public institutes, universities and private firms. In this paper, we analyze the structure of technology evolution in Korea with empirical data of patents to understand the prosperity of ICT sector in Korea. To do so, we define a technology network, or a set of nodes and links, representing technology fields and the relations between the fields, respectively, and measure the network topology and position per year between 1970 and 2010. Our results propose that the technology network maintains the scalefree topology, but the entities of the hub positions are gradually replaced emerging entities on the invariant network topology. Our findings are expected to motivate ICT innovation studies to understand the evolutionary mechanism of ICT industry in the systematic perspective of technology, and improve the policy of ICT innovation.
Keywords: 330; Industry Change; Information and Communication Technology; Network Analysis; Patent Analysis